Justice Delayed is Justice Denied: The Lord Nelson Case - Gibson, Gary (Ontario History)

(untitled) (The Ontario Historical Society, 2016)
In 1811, William and James Crooks of Niagara built the schooner Lord Nelson. A year later, that vessel was seized by the United States Navy for violating American law, beginning a case unique in the relations between the United States, Great Britain and Canada. Although the seizure was declared illegal by an American court, settlement was delayed by actions taken (or not taken) by the American courts, Congress and the executive, the Canadian provincial and national governments, the British government, wars, rebellions, crime, international disputes and tribunals. It was 1930 before twenty-five descendants of the two brothers finally received any money.